37th World Congress of Vine and Wine and 12th General Assembly of the OIV 2014
DOI: 10.1051/oivconf/201406001
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de obtención de híbridos de levaduras para vinificaciones a bajas temperaturas

Abstract: Resumen. Aunque S. cerevisiae (S.c.) es la especie históricamente asociada a la vinificación, S. uvarum (S.u.) e híbridos naturales entre estas especies también han sido descriptos en vinos fermentados a bajas temperaturas. S. uvarum presenta perfiles de fermentación diferenciales, caracterizados por elevadas concentraciones de glicerol y 2-fenietanol sin aumento del contenido deácido acético. Los objetivos del presente trabajo fue generar híbridos interespecíficos entre Sc y dos cepas de Su de diferente ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…S. eubayanus has been intensively studied for industrial applications, and also for the understanding of evolution, ecology, and population genomics of the Saccharomyces genus. This species was initially found in association with trees of the genus Nothofagus in Patagonia (Argentina) (Libkind et al, 2011) and subsequently found in other trees in Patagonia (Eizaguirre et al, 2018; Langdon et al, 2020; Nespolo et al, 2020; Origone et al, 2014). It is also distributed in Asia (Bing et al, 2014), North America (Eizaguirre et al, 2018; Langdon et al, 2020; Peris et al, 2016, 2023) and has recently been isolated from Europe (Bergin et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…S. eubayanus has been intensively studied for industrial applications, and also for the understanding of evolution, ecology, and population genomics of the Saccharomyces genus. This species was initially found in association with trees of the genus Nothofagus in Patagonia (Argentina) (Libkind et al, 2011) and subsequently found in other trees in Patagonia (Eizaguirre et al, 2018; Langdon et al, 2020; Nespolo et al, 2020; Origone et al, 2014). It is also distributed in Asia (Bing et al, 2014), North America (Eizaguirre et al, 2018; Langdon et al, 2020; Peris et al, 2016, 2023) and has recently been isolated from Europe (Bergin et al, 2022).…”
Section: Introductionmentioning
confidence: 96%